Increasing Student Learning Motivation Through Audio-Visual Learning Media of Nutritious Food Ingredients in Vlll Class SMPN 8 Banjarbaru - Jeki, Jeki; Rakhman, Arie; Putra, Trinaldi Andika (Empiricism Journal, 2026)
Although audio-visual media has been widely used to support student engagement, classroom action research that specifically examines its use in PJOK theoretical materials, especially the learning of nutritious foodstuffs with a focus on student learning motivation, is still very limited. This study aims to improve and describe the development of learning motivation of grade VIII students through the use of audio-visual media combined with interactive learning activities in learning nutritious foodstuffs at SMPN 8 Banjarbaru. This research uses Classroom Action Research (PTK) which is carried out in two cycles. The data collection technique used a learning motivation questionnaire (covering six indicators: attention, relevance, confidence, satisfaction, perseverance, and activeness), observation, and documentation. The subject of the study is 25 students in grade VIII of SMP Negeri 8 Banjarbaru even semester of the 2025/2026 academic year. Based on the pre-cycle results, 14 students (56%) were in the low category and 11 students (44%) were in the very low category. In Cycle I, 17 students (68%) were upgraded to the high category and 8 students (32%) were in the low category. In Cycle II, 22 students (88%) were in the very high category and only 3 students (12%) were in the low category. The findings show that the use of audio-visual media combined with interactive learning activities supports increased student learning motivation in learning nutritious foodstuffs in the observed classroom context.